Diseño de un material de apoyo para la enseñanza de la guía de la nueva clasificación de la enfermedad periodontal en la clínica de la universidad Antonio Nariño sede Cúcuta (2024)
At a global level, not only dental caries but also periodontitis has a high prevalence, in numerous epidemiological studies, it has been shown that more than 50% of Men and approximately 35% of women suffer from this condition (Payajo, 2019). The Periodontitis is a disease that has been increasing due to factors such as the growth of the population and the increase in tobacco consumption. This habit, together with the accumulation of bacterial plaque, is one of the main causes of this inflammatory condition that affects the gums and the bone tissue that supports the teeth (Cárdenas et al., 2021).